1984
DOI: 10.1063/1.864821
|View full text |Cite
|
Sign up to set email alerts
|

Plasma resistivity in the presence of a reversed-field pinch dynamo

Abstract: A global calculation of reversed-field pinch (RFP) plasma resistivities, ηw∥ and ηk∥, based on power balance and magnetic helicity balance, respectively, is discussed. For reasonable RFP beta values (β<0.1), ηk∥ provides an estimate of plasma resistivity parallel to the magnetic field, and agrees with the Spitzer resistivity within a factor of two. The expression (1−ηk∥/ηw∥) indictes the fraction of ohmic heating power absorbed by fluctuations in the discharge. An examination of 180 kA discharges on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 7 publications
2
39
0
Order By: Relevance
“…Ignition by ohmic heating is consistent with classical plasma resistivity and is a strong possiblility in the RFP because of the high current density. Classical plasma resistivity is observed in the experiment, 45 where the higher voltages required to drive current in RFPs relative to tokamaks being a result of geometric factors (i.e., higher pitch) rather than "anomalous " resistivity.…”
Section: Heatingmentioning
confidence: 91%
See 1 more Smart Citation
“…Ignition by ohmic heating is consistent with classical plasma resistivity and is a strong possiblility in the RFP because of the high current density. Classical plasma resistivity is observed in the experiment, 45 where the higher voltages required to drive current in RFPs relative to tokamaks being a result of geometric factors (i.e., higher pitch) rather than "anomalous " resistivity.…”
Section: Heatingmentioning
confidence: 91%
“…45 This demonstration is significant because it indicates how the plasma currents, and hence the confining fields, in an RFP may be sustained. All that is required is a means for replacing the helicity that is lost on the tlov resistive time scale (e.g., OFCD), and relaxation processes do the rest.…”
Section: C-26mentioning
confidence: 99%
“…(13). We found that it was necessary to operate the tokamak at relatively high edge q in order to provide a stable tokamak discharge that would not be terminated by spheromak injection.…”
Section: Zov-mentioning
confidence: 99%
“…͑19͒ and ͑22͒, it can be found that the term U؋B gives no contribution to the generation and dissipation of the mean magnetic field helicity. 81 In Eqs. ͑22͒ and ͑23͒, the ϩ sign expresses the helicity gain and the Ϫ sign the helicity loss.…”
Section: Fϭ␣bϫ␤"؋b ͑11͒mentioning
confidence: 99%